Land Use and Bobwhite Populations in an Agricultural System in West Tennessee - Jay H. Exum; Ralph W. Dimmick (National Quail Symposium Proceedings, 2017)
The efficacy of a computer assisted habitat evaluation system (IMGRID: Information Management on a GRID cell system) was tested on Ames Plantation in west Tennessee. Habitat characteristics and bobwhite (Colinus virginiana) population size were compared to delineate the effect of land use changes on bobwhites. Significant changes in land use occurred. Pastures decreased from 120.4 ha in 1966 to 35.0 ha in 1980, while soybeans increased from 102.4 to 193. 1 ha. Idle land decreased from 212.9 ha to 178.6 between 1966 and 1980. Bobwhite population size was negatively correlated with the area maintained in soybeans (r = -0.63) and positively correlated with pastures (r = 0.76) and idle land (r = O. 76). Multiple component analyses indicated highest use by bobwhites of (1) areas where idle land, forests, and agriculture came within close proximity, (2) areas near food plots, and (3) idle land alone. Single component analyses identified high use by bobwhites of idle land, wild herbaceous vegetation, and food plots. Within forests or idle land, bobwhites preferred areas containing honeysuckle,